A study on PEI among private dentists in Mashhad, Iran - Ali Labafchi; Amin Rahpeyma; Saeedeh Khajehahmadi (Journal of Family Medicine and Primary Care, 2020)
Aim: We aimed to identify the percutaneous exposure incident (PEI) by private dentists in Mashhad, Iran. Methods: Subjects included 199 dentists enrolled in this study. A questionnaire consisting of 11 questions was sent to the dentists for data collection. Information was collected on knowledge about dangers of PEI, a history of needlestick or sharps injuries over the past 12 months, types of devices causing the needlestick or sharps injuries, HBV vaccination, knowledge about PEI protective and therapeutic protocol, and reporting PEI to the specialist. The first ten questions were corrected and each sheet received a score ranging from 0 to 10. Result: 95 women (47.7%) and 104 men (52.3%) participated in this study aged between 27–72 years old. The findings showed that a total of 132 dentists (66.3%) had experiences with PEI. 45 (22.6%) of them had experiences with PEI in the past year. Files and needles were found to be the most frequent tools causing PEI, each with 29.7% of frequency. 16.6%, 8.6, 5.7, and 9.7% were obtained for dental burs, band, and surgical baled, respectively as other tools responsible for injuries. Results of the question about causes of needlestick injuries showed that personal carelessness is the most frequent reason (53.8%) followed by inappropriate disposal of the needles (7.6%). Conclusion: The personal carelessness and inappropriate disposal of needles were reported as the most common reasons for PEI injuries. It is suggested to educational programs for dentists should focus on preventing the PEI.